1980
DOI: 10.1021/i360073a025
|View full text |Cite
|
Sign up to set email alerts
|

New Rubber Peptizers and Coatings Derived from Guayule Resin (Parthenium argentatum Gray)

Abstract: Guayule resin is a byproduct of guayule rubber extraction and its commercial utilization could affect favorably the economics of guayule rubber production. A physical and chemical characterization of the resin has been made and degrading effects upon the rubber determined by viscometry, showing that the resin is a rubber prooxidant. This fact could be important in the field of rubber processing aids (peptizers). Coatings based on guayule resin have been developed which compare favorably in properties (abrasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…During this period, the rubber would require more rigorous antioxidant protection. Belmares et al (1980) suggested that the prooxidant properties of guayule resin could prove valuable in applications calling for rubber peptizers. In addition, resin-based coatings with good water resistance were obtained with formulations containing higher triglyceride levels.…”
Section: Resultsmentioning
confidence: 99%
“…During this period, the rubber would require more rigorous antioxidant protection. Belmares et al (1980) suggested that the prooxidant properties of guayule resin could prove valuable in applications calling for rubber peptizers. In addition, resin-based coatings with good water resistance were obtained with formulations containing higher triglyceride levels.…”
Section: Resultsmentioning
confidence: 99%
“…Resin contains mostly terpenes and lipids, but also several molecules belonging to other classes of compounds. The following have been reported: monoterpenes (α-pinene, camphene, β-pinene, α-phellandrene, β-phellandrene, sabinene, β-myrcene, limonene, terpinolene, β-ocimene, cadinene, dipentene, bornyl acetate) [ 52 , 53 , 54 ], sesquiterpenes esters (guayulins A, B, C, D), sesquiterpene alcohols [ 51 , 52 , 53 ], triterpenes (argentatins A, B, C, D, E, F, G, H) [ 55 , 56 ], alkaloids (guayulamines A, B) [ 57 ], organic acids (cinnamic acid) [ 58 ], phytosterols [ 55 ], triacylglycerols (fatty acids: palmitic, stearic, arachidic, myristic, oleic, linoleic, linolenic) [ 50 , 51 ], flavonoids, flavonoid glycosides [ 59 ], and carotenoids [ 53 ]. A patent directly tackles the separation of the isoprenic constituents of guayule by liquid-liquid partitioning [ 60 ].…”
Section: Chemical Composition Of Extractablesmentioning
confidence: 99%
“…The whole resin can be used as a wood preservative, against damage by Teredinidae and Limnoria sp., and particularly, against the very destructive Coptotermes termite species [107,108]. Resin shows a prooxidant activity, and it is especially interesting because prooxidants (or peptizers) are ordinarily toxic synthetic products [53]. It can also be used in the formulation of coatings and paints, bringing good properties (abrasion resistance, gloss, drying time, and water resistance) [11,53].…”
Section: Resinmentioning
confidence: 99%
“…In addition to rubber, guayule has very high resin content, up to 9% based on total dry matter (Dissanayake et al, 2004;Estilai, 1991;Banigan et al, 1982). Guayule resin has also been found to have economic potential as a termaticide (Nakayama, 2005;Nakayama et al, 2001;Bultman et al, 1998), wood preservative (Nakayama et al, 2001;Bultman et al, 1991;Chow et al, 2008), and an additive to epoxies and coatings (Th ames and Kaleem, 1991;Th ames and Wagner, 1991;Belmares et al, 1980). Banigan et al (1982) found that 15% of guayule biomass was resin, rubber, and wax.…”
mentioning
confidence: 99%